AUTONOMY IN THE TRANSITION FROM FOREIGN LANGUAGE LEARNING TO FOREIGN LANGUAGE TEACHING - BENSON, Phil; HUANG, Jing (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
This paper discusses the historical development of the concept of teacher autonomy in foreign language education and its relationship to the idea of learner autonomy. Three major phases in the development of conceptions of teacher autonomy are reviewed, involving attention to teacher roles in autonomous learning projects, professional development and professional freedom. Different ways of conceptualising the link between teacher and learner autonomy are discussed and an alternative conception based on the notion of transition from learner autonomy to teacher autonomy in learning-teaching careers is proposed.